Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
Keywords: dept.phy; peer-reviewed

Kepler-63b: A giant planet in a polar orbit around a young sun-like star - Sanchis-Ojeda, Roberto; Winn, Joshua N.; Marcy, Geoffrey W.; Howard, Andrew W.; Isaacson, Howard; Johnson, John Asher; Torres, Guillermo; Albrecht, Simon; Campante, Tiago L.; Chaplin, William J.; Davies, Guy R.; Lund, Mikkel N.; et al. (The Astrophysical Journal, 2013)
We present the discovery and characterization of a giant planet orbiting the young Sun-like star Kepler-63 (KOI-63, M⊙Kp = 11.6, T eff = 5576 K, M⊙ = 0.98 M⊙). The planet transits every 9.43 days, with apparent depth variations and brightening anomalies caused by large starspots. The planet's radius is 6.1 ± 0.2 R ⊕, based on the transit light curve and the estimated stellar parameters. The planet's mass could not be measured with the existing radial-velocity data, due to the high level of stellar activity, but if we assume a circular orbit, then we can place a rough upper bound of 120 M ⊙⊕ (3σ). The host star has a high obliquity (ψ = 104°), based on the Rossiter-McLaughlin effect and an analysis of starspot-crossing events. This result is valuable because almost all previous obliquity measurements are for stars with more massive planets and shorter-period orbits. In addition, the polar orbit of the planet combined with an analysis of spot-crossing events reveals a large and persistent polar starspot. Such spots have previously been inferred using Doppler tomography, and predicted in simulations of magnetic activity of young Sun-like stars. © 2013. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (Kepler-63); stars: rotation; starspots

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18, KIC 8644288, 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830, TOI-175); techniques: photometric